Concrete composition and concrete structure

By using cement, fly ash, hearthstone fine powder and diatom powder in concrete formulations and controlling the water coefficient, the shortcomings of concrete in the prior art in terms of mechanical properties and environmental impact are solved, and lower carbon dioxide emissions and better mechanical properties are achieved.

JP2025044058APending Publication Date: 2025-04-01TOHOKU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023151751
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing cement concrete formulas that reduce carbon emissions still have room for improvement in mechanical properties and environmental impacts, especially in further reducing carbon dioxide emissions.

Method used

A concrete formula containing cement, fly ash, hearthstone fine powder and diatom powder is used, and the water coefficient is controlled between 15% and 30%, to create concrete structures with excellent mechanical properties and reduced environmental impact through this formula.

Benefits of technology

Achieving a significant reduction in its carbon dioxide emissions while maintaining or improving the mechanical properties of concrete, providing a more environmentally friendly building materials solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044058000003
    Figure 2025044058000003
  • Figure 2025044058000004
    Figure 2025044058000004
  • Figure 2025044058000005
    Figure 2025044058000005
Patent Text Reader

Abstract

To provide a concrete composition excellent both in mechanical properties and environmental load properties, and a concrete structure comprising a hardened product thereof.SOLUTION: A concrete composition includes a binder, water, and an aggregate. The binder includes cement, fly ash, blast furnace slag fine powder, and silica fume, a content of the cement in the binder is 2 mass% or more and 5 mass% or less, a content of the fly ash is 60 mass% or less, a content of the blast furnace slag fine powder is 10 mass% or more and 75 mass% or less, and a content of the silica fume is 5 mass% or more and 30 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to concrete compositions and concrete structures. [Background technology]

[0002] Currently, the world is aiming to achieve carbon neutrality. Cement concrete is the most popular building material. However, cement, one of the main ingredients of cement concrete, emits a large amount of carbon dioxide during its production, so its use as it has been in the past is being questioned. For this reason, technological developments that do not use cement, such as geopolymer concrete that does not use cement and conversion to wooden structures, are being promoted.

[0003] On the other hand, for example, the Global Cement and Concrete Association (GCCA) has proposed aiming to reduce carbon dioxide emissions while continuing to manufacture and use a certain amount of cement and concrete. This is because, although wood and wood-based materials can be used in a wide range of applications as substitutes for concrete, there are certain limitations in terms of ensuring large cross-sections, rigidity, and fire resistance. Therefore, an extremely big breakthrough is needed to replace all concrete structures with wood and wood-based materials.

[0004] Therefore, concrete compositions have been developed that use a reduced amount of cement and an increased amount of admixtures such as blast furnace slag and fly ash as a cement substitute (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-006321 A [Patent Document 2] JP 2016-199443 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the concrete compositions described in Patent Documents 1 and 2 emit approximately 20% to 80% of the carbon dioxide emissions of ordinary concrete, and further reductions in carbon dioxide emissions are desired.

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a concrete composition which is excellent in both mechanical aspects and environmental load aspects, and a concrete structure made of the hardened product thereof. [Means for solving the problem]

[0008] The present invention has the following aspects. [1] A concrete composition comprising a binder, water, and aggregate, The binder includes cement, fly ash, ground granulated blast furnace slag, and silica fume; A concrete composition, wherein the binder contains the cement in an amount of 2% by mass or more and 5% by mass or less, the fly ash in an amount of 60% by mass or less, the ground granulated blast furnace slag in an amount of 10% by mass or more and 75% by mass or less, and the silica fume in an amount of 5% by mass or more and 30% by mass or less. [2] The concrete composition according to [1], wherein the water-binder ratio in the concrete composition is 15% or more and 30% or less. [3] Unit cement content is 100 kg / m 3 The concrete composition according to [1] or [2], [4] A concrete structure comprising a hardened concrete composition according to any one of [1] to [3]. Effect of the Invention

[0009] According to the present invention, it is possible to provide a concrete composition which is excellent in both mechanical aspects and environmental load aspects, and a concrete structure made of the hardened product thereof. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing the environmental and mechanical aspects of concrete. [Diagram 2] FIG. 13 is a diagram showing average values ​​of the results of compressive strength tests of test specimens in experimental examples. [Diagram 3] FIG. 13 is a diagram showing the results of calculating the amount of carbon dioxide emissions from test specimens in the experimental examples. [Figure 4] FIG. 13 is a diagram showing the mechanical performance evaluation value EMI per environmental load evaluation value of the test specimens in the experimental examples. [Diagram 5] FIG. 13 is a diagram showing the results of environmental impact assessment of the test specimens of the experimental examples, based on C100_30. [Figure 6] FIG. 1 is a diagram showing the results of analysis by XRD of a test specimen of an experimental example. [Figure 7] 1 is an SEM image of a test specimen of an experimental example. [Figure 8] FIG. 8 is a diagram showing the results of elemental analysis of (A)+ in FIG. 7. [Figure 9] FIG. 8 is a diagram showing the results of elemental analysis of (B)+ in FIG. 7. [Figure 10] 1 is an SEM image of a test specimen of an experimental example. [Figure 11] FIG. 11 is a diagram showing the results of elemental analysis of (A)+ in FIG. [Figure 12] FIG. 11 is a diagram showing the results of elemental analysis of (B)+ in FIG. [Figure 13] 1 is an SEM image of a test specimen of an experimental example. [Figure 14] FIG. 14 is a diagram showing the results of elemental analysis of (A)+ in FIG. [Figure 15] FIG. 14 is a diagram showing the results of elemental analysis of (B)+ in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] An embodiment of the concrete composition of the present invention and a concrete structure made of the hardened product thereof will be described below. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.

[0012] [Concrete composition] A concrete composition according to one embodiment of the present invention includes a binder, water, and aggregate.

[0013] The binder includes cement, fly ash, ground granulated blast furnace slag, and silica fume.

[0014] Examples of cement include low-heat Portland cement, ordinary Portland cement, and blast-furnace cement.

[0015] The cement content in the binder is 2% by mass or more and 5% by mass or less, and preferably 3% by mass or more and 4.5% by mass or less. If the cement content is less than the lower limit, the compressive strength is significantly reduced. If the cement content is more than the upper limit, the effect of reducing carbon dioxide emissions is smaller than the compressive strength obtained.

[0016] Examples of fly ash include fly ash raw powder, type II fly ash, and type I fly ash.

[0017] The content of fly ash in the binder is 60 mass % or less, and preferably 45 mass % or less. If the content of fly ash exceeds the upper limit, the compressive strength is significantly reduced.

[0018] The content of ground granulated blast furnace slag in the binder is 10% by mass or more and 75% by mass or less, and preferably 30% by mass or more and 60% by mass or less. If the content of ground granulated blast furnace slag is less than the lower limit, the compressive strength is significantly reduced. If the content of ground granulated blast furnace slag is more than the upper limit, the compressive strength is reduced.

[0019] Silica fume is an ultrafine activated silica by-product produced during the production of ferrosilicon or silicon metal in an electric arc furnace.

[0020] The content of silica fume in the binder is 5% by mass or more and 30% by mass or less, and preferably 10% by mass or more and 25% by mass or less. If the content of silica fume is less than the lower limit, the compressive strength is significantly reduced. If the content of silica fume is more than the upper limit, the concrete composition may not harden.

[0021] The water is not particularly limited as long as it is water that has been conventionally used in the production of concrete, and for example, tap water, groundwater, river water, seawater, or sludge water can be used. The water may be used alone or in combination of two or more kinds.

[0022] As aggregate, fine aggregate and coarse aggregate are used, but mortar can also be used without using coarse aggregate.

[0023] The fine aggregate is not particularly limited, but examples thereof include granulated blast furnace slag, molten coal ash slag (IGCC slag), natural sand, copper slag, nickel slag, steelmaking slag, and mixtures thereof.

[0024] The content of fine aggregate in the concrete composition is preferably 50 parts by mass or more and 300 parts by mass or less, more preferably 75 parts by mass or more and 200 parts by mass or less, based on 100 parts by mass of binder. If the content of fine aggregate is less than the lower limit, the amount of shrinkage becomes excessive. If the content of fine aggregate is more than the upper limit, construction becomes difficult.

[0025] The coarse aggregate is not particularly limited, but may be any coarse aggregate that is usually mixed with cement. Examples of the coarse aggregate include gravel, crushed stone, artificial coarse aggregate, slag coarse aggregate, and mixtures thereof.

[0026] The content of the coarse aggregate in the concrete composition is preferably 50 parts by mass or more and 300 parts by mass or less, more preferably 75 parts by mass or more and 200 parts by mass or less, based on 100 parts by mass of the binder. If the content of the coarse aggregate is less than the lower limit, the amount of shrinkage becomes excessive. If the content of the coarse aggregate is more than the upper limit, construction becomes difficult.

[0027] The concrete composition may contain chemical admixtures such as a water reducing agent, an air entraining agent, etc., as necessary. As the chemical admixture, a general chemical admixture used in the production of concrete structures can be used. The chemical admixtures may be used alone or in combination of two or more.

[0028] The water-binder ratio in the concrete composition of the present embodiment is preferably 15% or more and 30% or less, more preferably 20% or more and 25% or less. If the water-binder ratio is less than the lower limit, construction becomes difficult. If the water-binder ratio is more than the upper limit, sufficient compressive strength cannot be obtained.

[0029] The unit cement content in the concrete composition of this embodiment is 100 kg / m 3 It is preferable that:

[0030] According to this embodiment, it is possible to provide a concrete composition that is excellent in terms of both mechanical properties and environmental load.

[0031] [Method of manufacturing concrete composition] The concrete composition of the present embodiment can be produced by kneading a binder containing cement, fly ash, ground granulated blast furnace slag, and silica fume, water, and aggregate. The kneading method is not particularly limited, and can be carried out by a conventionally known method for kneading concrete compositions using a gravity mixer (tilt-type drum mixer, etc.), a forced mixing mixer (horizontal single-shaft type, horizontal double-shaft type, pan type, etc.), etc.

[0032] [Concrete structure] The concrete structure according to one embodiment of the present invention is made of a hardened product of the concrete composition according to one embodiment of the present invention. The form of the concrete structure according to this embodiment is not particularly limited, but examples thereof include curbstone blocks, underground structural frameworks that are less susceptible to carbonation, and indoor structural frameworks that are less susceptible to corrosion of reinforcing bars.

[0033] According to this embodiment, it is possible to provide a concrete structure that is excellent in terms of both mechanics and environmental load.

[0034] [Manufacturing method of concrete structures] The concrete structure of the present embodiment can be produced by pouring the concrete composition according to one embodiment of the present invention into a formwork and compacting it. EXAMPLES

[0035] The present invention will be described in more detail below with reference to experimental examples, but the present invention is not limited to the following examples.

[0036] [Materials and Mixtures Used] As a binder, low-heat Portland cement (LC, density 3.22 g / cm 3 ), ordinary Portland cement (NC, density 3.16g / cm 3 ) was used. As an admixture, fly ash (FA, density 2.20 g / cm 3 ), ground granulated blast furnace slag (GGBS, density 2.91g / cm 3 ) and silica fume (SF, density 2.20 g / cm 3 ) was used. As fine aggregate, crushed sand (produced in Soma-gun, Fukushima Prefecture, surface dry density 2.66 g / cm 3 , coarse grain ratio 2.94) and land sand (Watari-gun, Miyagi Prefecture, surface dry density 2.60g / cm 3 , coarse grain ratio 2.03) and a mixture (S, surface dry density 2.63g / cm 3 , coarse grain ratio 2.49) was used. Crushed stone (G, from Soma-gun, Fukushima Prefecture, surface dry density 2.68 g / cm) was used as coarse aggregate. 3, coarse grain ratio 6.70, maximum dimension 20 mm) were used. As an admixture, a high-performance water reducing agent (SP, polycarboxylic acid, density 1.05 g / cm 3 ) was used. The mix proportions of the concrete compositions are shown in Table 1. Note that the concrete compositions of Experimental Examples 1 to 8 all had a unit cement content of 100 kg / m 3 The result was as follows.

[0037] [Table 1]

[0038] [Experimental Example 1] A concrete composition C2 was prepared. The content of low-heat Portland cement in the binder was 2 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, and silica fume) in the binder was 98 mass%. The water-binder ratio (W / B) was set to 20 mass%. The content of the fine aggregate was set to 200 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 300 parts by mass per 100 parts by mass of the binder. An Omnimixer (volume: 5 L) was used to mix the concrete composition. The binder and fine aggregate were added to an omni mixer and dry mixed for 30 seconds, and then the coarse aggregate was added and dry mixed for 30 seconds. After that, water and admixtures were added and mixed for 3 minutes to obtain a concrete composition C2. The concrete composition C2 was poured into the formwork, and then demolded after 3 days to obtain a cylindrical test specimen having a diameter of 100 mm and a height of 200 mm. Two similar test specimens were prepared. The test specimens were steam cured at 90°C for three days.

[0039] [Experimental Example 2] A concrete composition C3 was prepared. The content of low-heat Portland cement in the binder was 3 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, and silica fume) in the binder was 97 mass%. The water-binder ratio (W / B) was set to 20 mass%. The content of the fine aggregate was set to 200 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 300 parts by mass per 100 parts by mass of the binder. In the same manner as in Experimental Example 1, a concrete composition C3 was obtained. Two test specimens were prepared in the same manner as in Experimental Example 1, and steam cured at 90° C. for three days.

[0040] [Experimental Example 3] A concrete composition C3.5 was prepared. The content of low-heat Portland cement in the binder was 3.5 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, and silica fume) in the binder was 96.5 mass%. The water-binder ratio (W / B) was set to 20 mass%. The content of the fine aggregate was set to 200 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 300 parts by mass per 100 parts by mass of the binder. In the same manner as in Experimental Example 1, a concrete composition C3.5 was obtained. Two test specimens were prepared in the same manner as in Experimental Example 1, and were subjected to steam curing at 90° C. for three days.

[0041] [Experimental Example 4] A concrete composition C4 was prepared. The content of low-heat Portland cement in the binder was 4 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, and silica fume) in the binder was 96 mass%. The water-binder ratio (W / B) was set to 20 mass%. The content of the fine aggregate was set to 200 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 300 parts by mass per 100 parts by mass of the binder. In the same manner as in Experimental Example 1, a concrete composition C4 was obtained. Four test specimens were prepared in the same manner as in Experimental Example 1, two of which were steam cured at 90° C. for three days, and the remaining test specimen was water cured for 28 days.

[0042] [Experimental Example 5] A concrete composition C4(1) was prepared. The content of ordinary Portland cement in the binder was 4 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, silica fume) in the binder was 96 mass%. However, in C4 of Experimental Example 4, the amount of fly ash was increased and the amount of ground granulated blast furnace slag was decreased. The water-binder ratio (W / B) was set to 20 mass%. The content of fine aggregate was set to 160 parts by mass per 100 parts by mass of binder. The content of the coarse aggregate was 190 parts by mass per 100 parts by mass of the binder. The binder and fine aggregate were added to an omni mixer and mixed dry for 30 seconds, water and admixtures were added and mixed for 1.5 minutes, and then the coarse aggregate was added and mixed for 30 seconds to obtain a concrete composition C4(1). Two test specimens were prepared in the same manner as in Experimental Example 1, and were subjected to steam curing at 90° C. for three days.

[0043] [Experimental Example 6] A concrete composition C4(2) was prepared. The content of ordinary Portland cement in the binder was 4 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, silica fume) in the binder was 96 mass%. However, in C4 of Experimental Example 4, the amount of ground granulated blast furnace slag was increased and the amount of fly ash was decreased. The water-binder ratio (W / B) was set to 20 mass%. The content of fine aggregate was set to 160 parts by mass per 100 parts by mass of binder. The content of the coarse aggregate was 190 parts by mass per 100 parts by mass of the binder. In the same manner as in Experimental Example 5, a concrete composition C4(2) was obtained. Two test specimens were prepared in the same manner as in Experimental Example 1, and were subjected to steam curing at 90° C. for three days.

[0044] [Experimental Example 7] A concrete composition C4(3) was prepared. The content of ordinary Portland cement in the binder was 4 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, silica fume) in the binder was 96 mass%. However, in C4 of Experimental Example 4, the amount of silica fume was reduced, and the amounts of fly ash and ground granulated blast furnace slag were increased. The water-binder ratio (W / B) was set to 20 mass%. The content of fine aggregate was set to 160 parts by mass per 100 parts by mass of binder. The content of the coarse aggregate was 190 parts by mass per 100 parts by mass of the binder. In the same manner as in Experimental Example 5, a concrete composition C4(3) was obtained. Two test specimens were prepared in the same manner as in Experimental Example 1, and were subjected to steam curing at 90° C. for three days.

[0045] [Experimental Example 8] A concrete composition C4(4) was prepared. The content of ordinary Portland cement in the binder was 4 mass%, and the content of admixtures (fly ash, ground granulated blast furnace slag, silica fume) in the binder was 96 mass%. However, the amount of silica fume was further reduced compared to Experimental Example 7, and the amounts of fly ash and ground granulated blast furnace slag were increased. The water-binder ratio (W / B) was set to 20 mass%. The content of fine aggregate was set to 160 parts by mass per 100 parts by mass of binder. The content of the coarse aggregate was 190 parts by mass per 100 parts by mass of the binder. In the same manner as in Experimental Example 5, a concrete composition C4(4) was obtained. Two test specimens were prepared in the same manner as in Experimental Example 1, and were subjected to steam curing at 90° C. for three days.

[0046] [Experimental Example 9] A concrete composition C100_30 was prepared. Only low heat Portland cement was used as the binder. The water-binder ratio (W / B) was set to 40 mass%. The content of the fine aggregate was set to 140 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 230 parts by mass per 100 parts by mass of the binder. In the same manner as in Experimental Example 1, a concrete composition C100_30 was obtained. Two test specimens were prepared in the same manner as in Experimental Example 1, and were subjected to underwater curing for 28 days.

[0047] [Experimental Example 10] A concrete composition C100_60 was prepared. Only low heat Portland cement was used as the binder. The water-binder ratio (W / B) was set to 34 mass%. The content of the fine aggregate was set to 140 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 230 parts by mass per 100 parts by mass of the binder. In the same manner as in Example 1, a concrete composition C100_60 was obtained. Two test specimens were prepared in the same manner as in Example 1, and were subjected to underwater curing for 28 days.

[0048] [Experimental Example 11] A geopolymer concrete composition GP was prepared. The binders used were 75% by mass of fly ash, 20% by mass of ground granulated blast furnace slag, and 5% by mass of silica fume. The water-binder ratio (W / B) was set to 40 mass%. The content of the fine aggregate was set to 200 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 300 parts by mass per 100 parts by mass of the binder. Geopolymer concrete composition GP was obtained in the same manner as in Experimental Example 1, except that an alkaline stimulant was used instead of the admixture so that the alkaline water molar ratio was 0.288 mol / mol. Four test specimens were prepared in the same manner as in Experimental Example 1, two of which were steam cured at 90° C. for three days, and the remaining test specimen was water cured for 28 days.

[0049] [Experimental Example 12] A geopolymer concrete composition LGP was prepared. The binders used were 75% by mass of fly ash, 20% by mass of ground granulated blast furnace slag, and 5% by mass of silica fume. The water-binder ratio (W / B) was set to 40 mass%. The content of the fine aggregate was set to 200 parts by mass per 100 parts by mass of the binder. The content of the coarse aggregate was 300 parts by mass per 100 parts by mass of the binder. Geopolymer concrete composition GP was obtained in the same manner as in Experimental Example 1, except that an alkaline stimulant was used instead of the admixture so that the alkaline water molar ratio was 0.04 mol / mol. Two test specimens were prepared in the same manner as in Experimental Example 1, and were subjected to steam curing at 90° C. for three days.

[0050] [Environmental impact assessment based on compressive strength tests and carbon dioxide emissions] A compressive strength test was carried out on the specimens of Experimental Examples 1 to 8. The compressive strength test was carried out in accordance with JIS A 1108, with the loading rate set to 0.6 MPa. Carbon dioxide emissions were calculated using the following formula (1). E = Σ(w × e / 1000) (1) In the above formula (1), E is the carbon dioxide emission (kg / m3), w is the unit mass of each material that composes the test specimen (kg / m3), and e is the carbon dioxide emission basic unit (kg / t) of each material that composes the test specimen. The unit mass values ​​shown in Table 1 and the carbon dioxide emission units shown in Table 2 were used. Here, we compared the carbon dioxide emissions of the materials alone, excluding the carbon dioxide emissions from transportation, mixing, steam curing, etc.

[0051] [Table 2]

[0052] The environmental impact assessment is calculated by the mechanical performance evaluation value (MI x ), and the environmental impact evaluation value (EI y ), and the mechanical performance evaluation value (EMI) per environmental load evaluation value was calculated using the following formula (4). MI x =MI / MI inf (2) E.I. y =EI sup / EI (3) EMI=MI / EI (4) In the above formulas (2) to (4), MI is the compressive strength (MPa), MI inf is the standard compressive strength (C100, 30MPa), EI is the carbon dioxide emission, EI sup is the standard carbon dioxide emission (C100, 320 kg / m 3 ). These values ​​are compared relative to the standard mechanical performance and environmental load, and the higher the value, the better the evaluation. As shown in Figure 1, the horizontal axis is the MI x , the vertical axis is EI y By doing so, it is possible to evaluate performance by dividing the materials into regions. In addition, since the evaluation is done by comparing with a reference material, the origin is set to (1, 1). In other words, materials included in region [3] in Figure 1 can be said to be superior in both environmental and mechanical aspects.

[0053] [Reaction mechanism investigated by XRD and SEM / EDS analysis] The components contained in the samples were examined based on X-ray peaks by X-ray diffraction (XRD). In addition, the elements constituting the samples and their distribution were investigated by SEM / EDS analysis. For the three types of cement, C100_30, C4, and GP, shown in Table 1, the paste from which the aggregate had been removed was ground in a mortar and used as the XRD sample. Separately, a cylindrical specimen with a diameter of 50 mm and a height of 100 mm was prepared and cut into 1 cm squares with a cutter, then cut in half with pliers to remove any dirt or scratches that might interfere with observation. Immediately afterwards, the cut surface was observed using SEM / EDS.

[0054] [Compressive strength evaluation results] The average values ​​of the results of the compressive strength tests of the specimens of Experimental Examples 1 to 12 are shown in Fig. 2. The specimens that were subjected to underwater curing are marked with "w". The compressive strength of C100_30 and C100_60 was roughly as expected. The compressive strength of C4 was 58.4MPa, and that of C4w was 35.2MPa. The strength development of the water-cured concrete was only 60.3% of that of the steam-cured concrete. In addition, the compressive strength decreased by about 20 MPa from C4 to C3. Furthermore, in C2, the concrete composition did not harden. Therefore, it is considered necessary for the binder to contain 3 mass% or more of low-heat Portland cement. Furthermore, it was confirmed that in C4(1) and C4(2), when either the fly ash or ground granulated blast furnace slag was excessively increased, the compressive strength was reduced compared to the original C4. Also, in C4(3) and C4(4), it was confirmed that when the amount of silica fume was reduced, the compressive strength was reduced compared to the original C4. In addition, the compressive strength of GP was 45.9 MPa, and that of GPw was 12.8 MPa. The strength development of the underwater cured concrete was only 27.9% of that of the steam cured concrete. Based on the results of compressive strength development by underwater curing, C4 is considered to be a concrete composition that is likely to develop compressive strength like ordinary concrete, unlike GP, although it has a low content of low-heat Portland cement. In addition, the compressive strength of LGP was 20.4 MPa, which was only 44% of that of GP.

[0055] [Estimated carbon dioxide emissions] The results of calculating the carbon dioxide emissions from the test specimens of Experimental Examples 1 to 12 are shown in FIG. It was confirmed that GP can significantly reduce carbon dioxide emissions compared to ordinary concrete. It was also confirmed that C4 can significantly reduce carbon dioxide emissions compared to GP. The reason for this is that the carbon dioxide emission unit of NaOH used as an alkaline irritant is 1143 kg / m 3 The carbon dioxide emission intensity of low-heat Portland cement is 766.6 kg / m 3 The points mentioned are bigger than that. For GP, 90.1 kg / m 3 AA must be used, while C2-C4 require 7.9 kg / m 3 ~15.9kg / m 3 The use of low-heat Portland cement allows for a significant reduction in carbon dioxide emissions. On the other hand, with GP, it is necessary to ensure the alkaline water molar ratio required to achieve compressive strength. In the case of LGP, where the AA content was reduced and the carbon dioxide emissions were set at the same level, the compressive strength was 20.4 MPa, less than half that of GP. Therefore, it is considered difficult to drastically reduce the AA content.

[0056] [Environmental Impact Assessment] The mechanical performance evaluation value EMI value per environmental load evaluation value is shown in Fig. 4. C4, C4w, C3.5, C3, and C2 are 1MPa×m 3 / kg, demonstrating that compressive strength can be achieved with a much lower environmental impact than GP. The results of the environmental impact assessment based on C100_30 are shown in Figure 5. In Figure 5, C100_60 is in [2] by region, while all but GPw and LGP are in [3]. This shows that C4, C4w, C3.5, C3, C2, and GP are superior in both environmental and mechanical aspects. In particular, C4 has nearly twice the compressive strength of C100_30, and reduced carbon dioxide emissions to about one-twelfth that of C100_30. Although C3.5 and C3 have lower compressive strength than C4, they achieve about 40 MPa, which is within the range of general design standard strength. From these results, when comparing the carbon dioxide emissions of the materials alone, excluding the carbon dioxide emissions from transportation, mixing, steam curing, etc., it appears that C4, C4w, C3.5, C3, and C2 are capable of achieving both a reduction in environmental impact and ensuring mechanical performance.

[0057] [Reaction mechanism investigation] By comparing C4w and GPw, it was confirmed that C4 is more likely to develop strength during underwater curing than GP. It is believed that this result occurred because low-heat Portland cement hardens through a hydration reaction, while GP hardens through a condensation polymerization reaction of the polymer. The results of the analysis by XRD are shown in FIG. 6. The results of the analysis by SEM / EDS are shown in FIG. 7 to FIG. 15. In FIG. 7, the "+" marks indicate the measurement points of the EDS analysis, FIG. 8 is a diagram showing the results of the elemental analysis in (A)+ of FIG. 7, and FIG. 9 is a diagram showing the results of the elemental analysis in (B)+ of FIG. 7. In FIG. 10, the "+" marks indicate the measurement points of the EDS analysis, FIG. 11 is a diagram showing the results of the elemental analysis in (A)+ of FIG. 10, and FIG. 12 is a diagram showing the results of the elemental analysis in (B)+ of FIG. 10. In FIG. 13, the "+" marks indicate the measurement points of the EDS analysis, FIG. 14 is a diagram showing the results of the elemental analysis in (A)+ of FIG. 13, and FIG. 15 is a diagram showing the results of the elemental analysis in (B)+ of FIG. 13.

[0058] In Fig. 6, the diffraction patterns of C4 and GP are compared, and it is confirmed that the positions of the peaks are roughly the same, while the graphs of C4 and C100 are compared, and that the positions of the peaks are different. Therefore, since C4 has peaks of quartz (Q) and mullite (M), it is considered to be a hardened concrete composition with crystalline components similar to GP. On the other hand, it can be seen that the halo of C4 is more mountain-shaped than that of GP at diffraction angles of 15deg to 25deg. Since the diffraction pattern of C4 (C4+AA), which has the same content of GP and AA, changes to a flat pattern like that of GP, it is considered that the product of C4, which contains non-crystalline components, is different from GP. In addition, it was confirmed that CSH exists in C100 at a diffraction angle of 29deg. Here, it is known that GP generates CASH, in which part of Si is replaced by Al, when granulated blast furnace slag is replaced. In addition, the CSH and CASH of GP and the CSH of low-heat Portland cement both contain SiO 4 Tetrahedron and AlO 4It is composed of a tobermorite structure in which two tetrahedral chains are connected to sandwich Ca-O. Furthermore, it has been confirmed that the diffraction angles at which the CSH and CASH peaks appear are roughly the same. Therefore, since C4 contains a lot of Al and the structure of the hardened bodies of cement and GP is similar, it is thought that C4 produces CASH hydrate in addition to CSH.

[0059] In Figures 8, 9, 11, 12, 14 and 15, it was found that C4 differs from GP in that it does not contain Na and that it has a Ca peak. GP solidifies as a product of sodium ions and potassium ions being incorporated into aluminosilicate, which is the product of the condensation polymerization reaction between silicate ions and aluminate ions. In addition, when Ca from ground granulated blast furnace slag is included, CSH and CASH are more likely to be formed than polymer bodies. Therefore, it is considered that C4 hardens by forming hydrates derived from low-heat Portland cement, rather than polymer bodies formed by condensation polymerization. From the above, it is considered that C4 is produced by the formation of CSH hydrates from Ca in low-heat Portland cement, as well as CASH hydrates from Ca in ground granulated blast furnace slag.

Claims

1. A concrete composition comprising a binder, water, and aggregate, The binder includes cement, fly ash, ground granulated blast furnace slag, and silica fume; A concrete composition, wherein the binder contains the cement in an amount of 2% by mass or more and 5% by mass or less, the fly ash in an amount of 60% by mass or less, the ground granulated blast furnace slag in an amount of 10% by mass or more and 75% by mass or less, and the silica fume in an amount of 5% by mass or more and 30% by mass or less.

2. 2. The concrete composition according to claim 1, wherein the water-binder ratio in the concrete composition is 15% or more and 30% or less.

3. Unit cement amount is 100 kg / m 3 3. The concrete composition according to claim 1 or 2, wherein:

4. A concrete structure comprising a hardened concrete composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Cement composition

    JP2011006321A

  • Cement composition

    JP2016199443A